2020
DOI: 10.1093/ndt/gfz274
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of citric acid-based bicarbonate haemodialysis on patient outcomes: a survival propensity score–matched study in western France

Abstract: Background Citric acid–based bicarbonate haemodialysis (CIT-HD) has gained more clinical acceptance over the last few years in France and is a substitute for other acidifiers [e.g. acetic acid (CH3COOH) and hydrochloric acid (HCl)]. This trend was justified by several clinical benefits compared with CH3COOH as well as the desire to avoid the consequences of the corrosive action of HCl, but a nationwide clinical report raised concerns about the long-term safety of CIT-HD. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The third study was a long-term, retrospective, observational study, including 1,132 incident patients starting dialysis over a time span of 10 years, from 2008 to 2018, in five sanitary territories in the western region of France with a high prevalence of citric acid-containing dialysate citrate (57% in 2018). Again, comparing patients who spent >80% their dialysis time on citric acid-based dialysate to those who have never been exposed, the exposure to citric acid-containing dialysate up to a 6-year period showed no significant difference in all-cause mortality (33). Finally, the fourth study reported the results of a questionnaire survey sent to 1300 French dialysis units (34).…”
Section: Discussionmentioning
confidence: 99%
“…The third study was a long-term, retrospective, observational study, including 1,132 incident patients starting dialysis over a time span of 10 years, from 2008 to 2018, in five sanitary territories in the western region of France with a high prevalence of citric acid-containing dialysate citrate (57% in 2018). Again, comparing patients who spent >80% their dialysis time on citric acid-based dialysate to those who have never been exposed, the exposure to citric acid-containing dialysate up to a 6-year period showed no significant difference in all-cause mortality (33). Finally, the fourth study reported the results of a questionnaire survey sent to 1300 French dialysis units (34).…”
Section: Discussionmentioning
confidence: 99%
“… 32 When CAD was introduced in France, the average dialysate calcium increased to a larger extent than that observed in our study, and it has been suggested that this increase potentially helped to reduce changes in bone mineral metabolism markers, including iPTH. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Kossmann et al [ 57 ] observed an improved eKt/V in 142 HD patients treated for 6 months with citrate dialysis. In January 2020, French registry data about citrate dialysis have been published; survival analysis of 700 patients showed a trend toward a benefit in citrate dialysis that did not reach statistical significance ( p = 0.06) and remained not significant in the multivariate analysis [ 58 ]. Of note, citrate patients had a significantly lower erythropoietin resistance index despite having lower albumin levels and being more often treated with ACE-inhibitors (a drug class associated with erythropoietin resistance).…”
Section: From Delphi Approach To the Real Life In Dialysis Units: Des...mentioning
confidence: 99%